Implementation Of Death Crime Executions for Class I Narcotics Distributors - Susanto, Hadi; Pratiwi, Siswanti; Marbun, Warasman (International Peneliti Ekonomi, Sosial dan Teknologi, 2024)
The enactment of Law Number 35 of 2009 concerning Narcotics, types of Psychotropics class I and class II as stated in the attachment to Law Number 5 of 1997 concerning Psychotropics have been moved to Narcotics class I in Law Number 35 of 2009 concerning Narcotics and the attachment regarding types of Psychotropics class I and class II in Law Number 5 of 1997 concerning Psychotropic Substances are revoked and declared invalid. With this figure, the level of narcotics use in Indonesia is the largest in Asia. Indonesia is considered a drug emergency, the process of executing the death penalty does not have a deterrent effect on drug dealers or smugglers. The problem is, how to carry out the execution of the death penalty for class I narcotics dealers and what are the obstacles to not immediately carrying out the death penalty for class I narcotics dealers. The research method used is Empirical Normative Legal Research. In conclusion: The death penalty imposed by a court in a general court or military court environment is carried out by being shot to death. This provision does not reduce existing provisions in the criminal procedural law regarding carrying out court decisions. Based on Law No. 35 of 2009 concerning Narcotics. And the factors that cause obstacles in the implementation of the death penalty include legislative factors (legal substance), law enforcement factors, means and facilities factors, and community factors.